Rancang Bangun Aplikasi Ensiklopedia Makanan Tradisional Bugis Beserta Cara Pembuatannya Berbasis Android - Sudirman, Sudirman; Masnur, Masnur; Yasin, Subarja (Jurnal Sintaks Logika, 2021)
The shift in consumer interest from traditional food to fast food is because the level of knowledge about traditional food has decreased from generation to generation. This is very concerning, considering that they are the younger generation who should be able to protect and preserve their ancestral heritage. In this day and age, many people have a hobby of cooking. Many media can be used to channel this hobby, one of which is reading books containing recipes, watching cooking television shows, searching for cooking sites and also taking existing cooking courses. Indeed, this method is quite troublesome, but in line with the advancement of technology that is increasingly developing, now these things can be done by mobile, including by using a cell phone. The need for a cellphone equipped with an operating system like a computer, practically the capabilities of this cellphone can almost match a computer, especially its ability to be able to install various applications from third parties to support the needs of its users. The results of the introduction application are to find out information from a traditional bugis food and the meaning contained therein which is based on android to simplify the learning process.